ANALISIS BAURAN PEMASARAN DALAM MENINGKATKAN TINGKAT HUNIAN KAMAR PADA FOUR POINTS BY SHERATON BALI, KUTA - Ni Luh Ayu Sara Pertiwi; I Wayan Kartimin; I Ketut Sutapa (Journal of Tourism and Interdiciplinary Studies, 2021)
This research is to analyze strategies that must be carried out by Four Points by Sheraton Bali, Kuta to increase sales volume. The analysis technique used in this study is a SWOT analysis technique consisting of IFAS, EFAS, IFE, EFE, and IE. The procedure for collecting data uses the method of observation, interviews, and surveys. The sample used in this study is purposive sampling technique where the respondents consisted of 10 people, the Director of Sales and Marketing ( respondents 1), Director of Operation (respondents 2), Account Sales Manager (respondents 3), Executive Sales (respondents 4), Sales Admin (respondents 5), Digital Marketing Manager (respondents 6), Marketing Comuncation Manager (respondent 7), Graphic Designer (respondent 8), Reservation (respondents 9 and 10). The results of this research are Four Points by Sheraton Bali, Kuta in column I, where the right strategy is market penetration strategy, market development strategy, product development strategy. The implication of this research is that it can be used as a reference in maintaining the sustainability of Four Points by Sheraton Bali, Kuta.